Uso de micro-ondas na fixação química de CO₂: revisão de estratégias sustentáveis para síntese orgânica - Souza, Demetrius Pereira de (Universidade Federal de São Carlos, 2026)
Carbon dioxide (CO₂) is one of the main gases responsible for the greenhouse effect and climate change. Although it is one of the major contributors to global warming, CO₂ can also be used as an abundant and renewable feedstock for the production of higher-value compounds, however, its high chemical stability makes this use challenging. The use of microwave irradiation in organic reactions has emerged as a practical and efficient alternative, since reactions often proceed faster, more selectively, and with lower energy consumption. Thus, this work presents a literature review on advances in the application of microwaves to the chemical fixation of CO₂, focusing on the production of cyclic carbonates, ureas, carbamates, and related derivatives. In addition, the main catalytic systems, the role of the dielectric properties of the reaction medium, and the operational limitations of this technology are discussed, although challenges related to scale-up, selectivity, and industrial feasibility still remain.
Use of microwaves in the chemical fixation of CO₂: A review of sustainable strategies for organic synthesis
Keywords: CO₂; Síntese assistida por Micro-ondas; Química verde; Catálise sustentável; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::SINTESE ORGANICA; 9. Indústria, Inovação e Infraestrutura; 12. Consumo e Produção Responsáveis